2023
DOI: 10.3390/brainsci13030375
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and Neuropsychological Indices of Cognitive Dysfunction in Patients with Chronic Insomnia and Severe Benzodiazepine Use Disorder

Abstract: Benzodiazepine (BDZ) misuse is a growing health problem, with 1–2% of patients under BDZ treatment meeting the criteria for use disorder or dependence. Although BDZ addiction potential has been known for decades, much remains unknown its effects on brain functions. The aim of this study was to assess the neuropsychological and neurophysiological profile of a group of chronic insomniacs taking long-term high doses of benzodiazepine. We recruited 17 consecutive patients admitted to our third-level Sleep Medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The results seemed to support the evidence for several cognitive models of insomnia, with a potential utility for the clinical assessment of insomnia. In a similar way, Castelnovo et al [3] present the neuropsychological and neurophysiological assessment of a group of chronic insomniacs and long-term, high-dosage benzodiazepine (BDZ) treatment. This cross-sectional study revealed a specific frontal dysfunction in their unique sample and should reinforce the vulnerability of the prefrontal cortex due to sleep loss or disturbed sleep.…”
mentioning
confidence: 99%
“…The results seemed to support the evidence for several cognitive models of insomnia, with a potential utility for the clinical assessment of insomnia. In a similar way, Castelnovo et al [3] present the neuropsychological and neurophysiological assessment of a group of chronic insomniacs and long-term, high-dosage benzodiazepine (BDZ) treatment. This cross-sectional study revealed a specific frontal dysfunction in their unique sample and should reinforce the vulnerability of the prefrontal cortex due to sleep loss or disturbed sleep.…”
mentioning
confidence: 99%